RECESSION: GOVERNMENT POLICY RESPONSE AND INEQUALITY- IS THERE A LINK? - H. Goldsmith, Arthur; Ullah Khan, Safdar (The journal of contemporary issues in business and government, 2022)
Economic inequality within countries throughout the world is striking and has increased over the past 3 decades. Moreover, recessions are common and are often influenced by global interconnections. In this essay, we set out standard economic ideas on ways public policy might respond to a recession and how these policies might exacerbate or mitigate economic inequality. In addition, we present evidence on the link between government behaviour and inequality for the group of OECD nations, to shed some light on the potential role of government in advancing inequality.